Analysis on the evolution of frost heaving pressure of penetrating crack considering water content and migration. (January 2023) - Zhang, Shengwen; Lin, Hang; Chen, Yifan; Wang, Yixian; Zhao, Yanlin
Frozen heaving failure of fractured rock mass is commonly encountered in engineering in cold regions, which is chiefly caused by the frost heaving pressure arising from the water–ice phase change in the crack. To explore the evolution of frost heaving pressure in penetrating elliptical crack considering water content and water migration, a new theoretical model embodying the frost heaving pressure evolutionary character was established by introducing freezing ratio function. The equivalent thermal expansion coefficient was used to analyze the evolution process of frost heaving pressure under the effect of water–ice phase change, which was then verified. It was found that the evolution process of frost heaving pressure can be divided into three stages: free expansion stage of water–ice phase change, rapid growth stage of frost heaving pressure, and stable stage of frost heaving pressure. Subsequently, the influences of rock thermal expansion effect, properties of rock and ice, and water content of crack on the frost heaving pressure were investigated. The results indicate that the impact of rock thermal expansion on frost heaving pressure is extremely slight, which is negligible. Comparing with the properties of rock, the properties of ice show significant effects on the frost heaving pressure, particularly the Poisson ratio of ice. In the case of identical water migration ratio, the peak frost heaving pressure increases linearly with the water content of crack.